Urban Flood Disaster Simulation and Inundation Impact on Nanning Based on Land-Pipe-River Coupling Model - CHENG Jianzhong; HUANG Yongjun; XU Bingqing (Renmin Zhujiang)
Nanning, as the capital of Guangxi Zhuang Autonomous Region, frequently experiences urban waterlogging disasters due to extreme rainfall events. To accurately simulate flood disasters in the urban area of Nanning and enhance flood risk prevention and control, this paper uses MIKE+ software to build a land-pipe-river coupling model for flood simulation and inundation impact analysis. This study conducts simulations on surface disaster-bearing bodies, underground pipelines and urban rivers, and evaluates the impacts brought by inundated disaster-bearing bodies based on the inundation area. The research results show that when urban flooding occurs due to rainfall events with return periods of 5 to 200 years, the inundation area gradually increases from 11.450 to 14.766 km², the inundation duration increases from 14.40 to 14.98 hours, the average inundation depth increases from 0.84 meters to 0.99 meters, the affected population grows from 54 747 to 70 601, and the GDP in affected regions rises from 1 068.72 to 1 378.22 million yuan. This study provides scientific evidence for flood prevention and drainage efforts in Nanning and also offers a reference for urban flood disaster simulations in other cities.